Laparoscopic management of chylous ascites posthiatal hernia repair with Toupet fundoplication - Adele Hwee Hong Lee (Journal of Minimal Access Surgery, 2020)
We present a case of chylous ascites in a 69-year-old man 5 months after a laparoscopic Toupet fundoplication (posterior 270°). This was successfully treated with laparoscopic ligation of tissue adjacent to the right crus. Laparoscopic ligation is a management option that should be considered after this rare complication, offering rapid results.